Fluidization behavior of biomass - Woo, Bo Yang. (2010)
The focus of this project is to investigate the fluidization behavior of biomass in a gassolid fluidization, while determining several variables that affects the fluidization of the biomass particles. The fluidization experiments are conducted with saw dust being the bed material. It was established that the overall sphericity of the saw dust particles are about 0.2, and subsequently, the minimum fluidization velocity of the bed was estimated to be about 0.233 m/s. It was also observed that the saw dust bed exhibit characteristics such as channeling and plugging, even though it belongs to Group B (according to Geldart’s Classification of Powders). It was then concluded that further improvements in the equipment for subsequent studies should be made to achieve better results for a more in-depth analysis.